P225 Day of admission results predict failure of first-line treatment in acute ulcerative colitis. (25th January 2019) - Grant, R; Lynch, R; Bouri, S; Elosua González, A; Manship, T; Jagger, F; Shivakumar, M; Satsangi, J; Ho, G-T; Lees, C; Plevris, N; Tozer, P; et al.
Abstract: Background: Intravenous (IV) steroids remain the standard first-line treatment for patients admitted with acute ulcerative colitis (UC). However, 30% of patients fail to respond and require second-line therapies and/or surgery. The purpose of this study was to determine whether Day 1 parameters could identify a group at high risk of failing first-line therapies. Methods: All admissions for acute UC (ICD-10 K51) to hospitals in NHS Lothian (4 sites) and St Mark's Hospital, Harrow from 1/11/11 to 31/10/16 were obtained from the regional coding departments. Case record review was performed. Response to IV steroids was defined as discharge from hospital with no further acute medical or surgical treatment. Non-response was defined as need to escalate to ciclosporin, infliximab, other acute therapy, or to have surgery. The following parameters were recorded for the first 10 days post admission: haemoglobin (Hb), platelet count, CRP, albumin, stool frequency and faecal calprotectin. Each patient was later attributed a score based on CRP (≤50 mg/dl = 0; >50 mg/dl = 1), albumin (≥30 g/l = 0; < 30 g/l = 1) and platelets (≤400 × 10 9 /l = 0; >400 × 10 9 /l = 1). Results: In total, 592 admissions with acute UC were identified; 391/592 (66%) responded to steroids, 201/592 (34%) patients were non-responders. 44 (22%) non-responders received infliximab as second-line therapy, 108 (54%) cyclosporine, and 4 (2%) other. Eighty-three (41%) non-responders required surgery; 7 (8%) had infliximab prior to surgery; 35 (42%) cyclosporine; 12 (14%) went straight to surgery. Insufficient data were available regarding 33 patients. On univariate analysis, albumin ( p = <0.001), platelet count ( p = 0.004) and CRP ( p = <0.001) were significantly different between responders and non-responders. On multi-variate analysis platelets were not significant. No difference was seen for Hb or stool frequency. 64.3% of patients with concurrent hypoalbuminaemia, high CRP and high platelets (score = 3) were non-responders. Conclusions: A third of patients failed to respond to IV steroids. Day of admission albumin, CRP and platelets significantly predicted failure of first-line therapy. 64.3% of patients with a score of 3 failed first-line medical therapy. The combination of these readily available parameters identifies a high-risk population who may benefit from earlier second-line medical or surgical intervention.